„Odkrycie” kodeksu Liwiusza z kościoła św. Piotra i Pawła w Legnicy na tle tradycji rękopiśmiennej Ab urbe condita i jego echa w prasie brytyjskiej w 1870 r. - Broda, Michał (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The work Ab urbe condita by Roman historian Titus Livius originally consisted of 142 books, of which 35 survived until today. Beginning in the Renaissance period, humanists and ancient historians persisted in attempts to find the lost books; once in a while, news of actual or alleged discoveries appeared.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne